Comparison the physicochemical properties of bunch press fibre cellulose and cyclone fibre cellulose of waste from industry Crude Palm Oil (CPO) - Irfan Gustian; Eka Angasa; G Ghufira; M Miliani; H Hairulumah (International Journal of Science and Engineering, 2014)
Study on comparison the physicochemical properties of bunch press fibre cellulose (Bpfc) and cyclone fibre cellulose (Cfc) wastes from industry Crude Palm oil (CPO) have been performed. The physicochemical properties both of celluloses have been done such as the average degree of polymerization (DP), solubility properties, functional group analysis, thermal properties and X-ray diffraction patterns. The average degrees of polymerization (DP) have been obtained 2195 and 567 for Bpfc and Cfc. Bunch press fibre cellulose and cyclone fibre cellulose were soluble in cupriethylenediamine (CED). FT-IR analysis showed the same pattern of spectrum but different intensities. Thermal stability of bunch press fibre cellulose and cyclone fibre cellulose remains stable up to a temperature of 250 °C. Glass transition bunch press fibre cellulose greater than the glass transition cyclone fibre cellulose and X-ray diffraction pattern shows the same pattern and intensity varies.